2014
DOI: 10.1039/c4ra05322b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in thermoelectric materials and solar thermoelectric generators – a critical review

Abstract: Thermoelectric materials have been extensively used in space satellites, automobiles, and, more recently, in solar thermal application as power generators. Solar thermoelectric generators (STEGs) have enjoyed rapidly improving efficiency in recent years in both concentrated and non-concentrated systems. However, there is still a critical need for further research and development of their materials and systems design before this technology can deployed for large-scale power generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 146 publications
(224 reference statements)
0
76
0
1
Order By: Relevance
“…1,2 The efficiency of TE conversion is mostly determined by the materials' dimensionless gure of merit, zT ¼ S 2 T/rk, where S, T, r and k are the Seebeck coefficient, absolute temperature, electrical resistivity and thermal conductivity, respectively. 6,7 Among these candidates, many binary and multinary selenides with low k have been found to exhibit promising zT values, such as the layered oxide BiCuSeO, 8,9 liquid-like Cu 2Àx Se 10,11 and the recently reported SnSe. Consequentially searching for and developing high-performance TE materials free of Te has become a popular trend in this eld.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The efficiency of TE conversion is mostly determined by the materials' dimensionless gure of merit, zT ¼ S 2 T/rk, where S, T, r and k are the Seebeck coefficient, absolute temperature, electrical resistivity and thermal conductivity, respectively. 6,7 Among these candidates, many binary and multinary selenides with low k have been found to exhibit promising zT values, such as the layered oxide BiCuSeO, 8,9 liquid-like Cu 2Àx Se 10,11 and the recently reported SnSe. Consequentially searching for and developing high-performance TE materials free of Te has become a popular trend in this eld.…”
Section: Introductionmentioning
confidence: 99%
“…Their applications in Dye Sensitized Solar Cells (DSSC) (Bella et al, 2015), energy storage and conversion (Griffini et al, 2014(Griffini et al, , 2013 have been reported recently. Encapsulation technology is widely used for various SPV technologies and systems such as Solar Thermoelectric (Sundarraj et al, 2014), silicon carbide (SiC) based SPV cells (Cheng et al, 2015), flexible polymer SPV cells (Moaven et al, 2015). Polymeric materials are most commonly used for encapsulation of c-Si SPV modules.…”
Section: Introductionmentioning
confidence: 99%
“…Development of thermoelectric materials with high figures of merit (ZT) is one of the challenging areas of research for the utilization of solar energy. Table 1 represents a comparison of the amount of energy (TW) produced from different forms of energy resources [10].…”
Section: Introductionmentioning
confidence: 99%